A strategy for improvement of the Cpk of DRAM modules in the depanel process of PCBA. (29th December 2006) - Lin, Zone-Ching; Ho, Chih-Yuan
This paper is to improve the dimensional accuracy of Small Outline Dual Inline Memory Modules (SO-DIMMs), which is a kind of Dynamic Random Access Memory (DRAM) modules for notebook computer, in the depanel process. This study proposes the implementation of combining grey relation analysis with Statistical Process Control (SPC) analysis, so as to quickly search the result that progressive tool wear is the dominant parameters adversely influencing the accuracy in the depanel process. To resolve tool wear issue, this paper implements the pretreated milling for a certain working distance before practically proceeding the depanel process. The accuracy of products, therefore, appears to be feasibly controllable. Furthermore, this study adopts SPC analysis to evaluate the improvement effect, revealing that Cpk value dramatically increases from 0.788 to 2.175, and the tool life of mill can also be extended from milling of 25 to 45 panels. It has also been successfully implemented in an international factory, resulting in a yield of more than 1 million DRAM modules.